Women's Economic Empowerment in Turkey - Çelik, Onur Burak; Yenilmez, Meltem Ince. (Milton : Routledge, 2019)
Turkey has experienced growth in both the population and the workforce. However, female participation in the workforce in Turkey is extremely low, largely due to financial dependency and lack of higher education. The authors argue that greater research is needed to improve the economic position of women throughout the country, and this remains a challenge that must be fixed both culturally and socioeconomically. The book explores the significant gap between policy advancements, actual practices, and the impact of regional variety in the cultural structure. The authors suggest that this in turn has affected Turkey's ability to implement changes and reform. Reform must allow women to pursue changes that will give them greater financial flexibility and freedom within the country. The authors demonstrate the concept and framework for women's empowerment and explore the need for this. This book seeks to discuss the approaches and strategies for empowering women by outlining the strategies, policies and tools that women are using for their empowerment focusing on Turkey while comparing with other countries worldwide. It also brings several issues to the forefront such as equality treatment, political participation, social issues, the gender pay gap, the glass ceiling and gender (in)equality, the migration effect and education. Offering a multi-disciplinary exploration of the relationship and connection between employment, national policies, migration economies, entrepreneurialism and gender in present Turkey, this book is an invaluable contribution to the existing literature surrounding Turkish gender studies and will be of interest to both scholars and experts in the field.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Women -- Employment -- Turkey; Women -- Turkey -- Economic conditions; Women -- Turkey -- Social conditions; BUSINESS & ECONOMICS / Labor; POLITICAL SCIENCE / Labor & Industrial Relations; BUSINESS & ECONOMICS / Development / Economic Development; SOCIAL SCIENCE / Gender Studies; BUSINESS & ECONOMICS / Economic Conditions